Effects of resistance training and soy isoflavone on body composition in postmenopausal women - Orsatti, Fábio Lera [UNESP]; Nahas, Eliana Aguiar Petri [UNESP]; Nahas Neto, Jorge [UNESP]; Maestá, Nailza [UNESP]; Orsatti, Cláudio Lera [UNESP]; Fernandes, César Eduardo (Wiley, 2010)
Objective. To investigate the independent and additive effects of resistance training (RT) and soy isoflavone (ISO) on body composition in postmenopausal women (PW). Method. This study used a placebo-controlled, double-blind (soy), randomized (ISO versus placebo) × (RT versus No RT) design. A total of 80 PW, aged 45–70 years, were randomly (71 completed 9-months intervention): RT + ISO (n = 15), No RT + ISO (n = 20), RT + placebo (n = 18), and No RT + placebo (n = 18). ISO received 100 mg a day of isoflavone; and to RT attended supervised resistance training sessions. At baseline and 9-months, fat and muscle mass were estimated by DXA. ANOVA and test t were used. Results. RT groups showed significantly increased muscle strength (35.2%) and muscle mass (1.4%). Exercising attenuated gains in fat trunk and % body fat (P<.05). Significant decreases in muscle mass (−1.8%) and increases in fat mass of the whole-body (1.6%) and trunk (9.7%) was found in no-RT groups (P<.05). In ISO groups, there were no differences in body composition and muscle strength. ISO and RT had no additive effects. Conclusion. In PW: RT improved muscle mass and strength and attenuated gain of fat mass; ISO did not alter body composition and muscle strength; there were no additive effects of RT and ISO.